Ordinances Ordained and Established by the Mayor & City Council of the City of New Orleans 68 (1817) - (:unkn) unknown (My University, 1817)
12: No person shall hereafter be permitted to fire or discharge any gun, pistol, fowling piece or firearm, nor to discharge or let off any rocket, cracker, squib or other fire-works, in any street, court yard, lot, walk or public way, within the city or suburbs, or from the door or window of any house or other building, or near any house or other inhabited part of said city or suburbs, on any account whatever particularly on the occasion of festivals or public rejoicings, under the penalty of from five to ten dollars upon each offender,
Keywords: DISCHARGE